Building Resilient MSMEs through Accounting Digitalization and Financial Competency Enhancement to Support the People's Economy - Salsabila Dwi Fitri (Dinasti Publisher, 2025)
The development of digital technology has brought significant changes in accounting practices, especially for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. On the other hand, human resource (HR) competence is an important factor in utilizing this technology to improve the quality of financial reports. This article aims to examine the role of accounting digitalization and HR competence on the quality of MSME financial reports in Indonesia through a systematic literature review approach. The method used is a literature review with a Systematic Literature Review (SLR) approach, which examines various relevant previous studies. The results of the study indicate that the effective implementation of accounting digitalization, if supported by competent HR, contributes greatly to increasing the transparency, accuracy, and reliability of MSME financial reports. This study is expected to be the basis for forming hypotheses in further empirical research and provide policy recommendations that encourage strengthening the digital capacity and HR of MSMEs in Indonesia.